The Correlation between Religiosity and Adversity Quotient of Islamic Education Students of Universitas Muhammadiyah Yogyakarta - Iqbal Fallawarukka, Andi Muhammad (Journal of Islamic Education and Ethics, 2024)
This research aims to: 1) Analyze the religiosity of Islamic Education students of the University of Muhammadiyah Yogyakarta batch 2019. 2) Analyze the adversity quotient of Islamic Education students of Universitas Muhammadiyah Yogyakarta of 2019. 3) Analyze the correlation between religiosity and adversity quotient of Islamic Education students of Universitas Muhammadiyah Yogyakarta of 2019. The type of this research was correlational research with a quantitative approach. The population of this research was active students of Islamic Education of Universitas Muhammadiyah Yogyakarta, a total of 157 students. The sample was taken from 113 respondents through a simple random sampling technique. The result showed that: 1) The religiosity of Islamic Education students of UMY of 2019, as evident from the total sample of 113 out of 157, was in an average category of 74%. 2) The adversity quotient of Islamic Education students of UMY of 2019, as evident from the total sample of 113 out of 157, was in an average category of 64%. 3) The hypothesis claiming that there is a positive correlation between religiosity and adversity quotient among Islamic Education students of UMY was accepted. This acceptance was based on the result of the correlation test, which indicated a Sig. Value of 0,000 < 0,05 and correlational coefficient (r) value of 0,602. Thus, it was concluded that the higher the religiosity of the Islamic Education students of UMY Batch 209 is, the higher their adversity quotient is. Consequently, the lower the religiosity of the Islamic Education students of UMY of 209 is, the lower their adversity quotient is.